2015
DOI: 10.1007/s12011-015-0255-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the mRNA Expression Pattern of Zn Transporters: a Probable Mechanism for Cadmium Retention and Zinc Redistribution in the Suckling Rat Tissues

Abstract: The present study was conducted to provide potential mechanism that may be responsible for Cd retention and Cd-induced Zn redistribution in tissues of suckling rat. For this purpose, suckling rats from mother receiving either tap water, Cd, or Cd + Zn during lactation period were sacrificed on postnatal day (PND) 14 and PND 21 for performing chemical and molecular analysis. Our results show that Cd exposure, although it does not affect the milk consumption, it clearly alters the lactational transfer, absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…In fact, during the lactation period, Cd is thought to be transported from maternal plasma to mammary gland and secreted into breast milk as well as essential element like Zn. Our previous study [15] imply that the downregulation of ZnT as well as the overexpression of ZIP transporters in the mammary gland of lactating rat and in the intestine of their offspring, play a major role in Cd accumulation and Zn redistribution in tissues of suckling rats. Zn testicular depletion during lactation seems also to be due to its sequestration by Cd-induced hepatic metallothioneins (MTs) from the plasma in the organism of offspring rats, thereby increasing its concentration in the liver and kidneys and probably restricting Zn supply to other tissues [18].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In fact, during the lactation period, Cd is thought to be transported from maternal plasma to mammary gland and secreted into breast milk as well as essential element like Zn. Our previous study [15] imply that the downregulation of ZnT as well as the overexpression of ZIP transporters in the mammary gland of lactating rat and in the intestine of their offspring, play a major role in Cd accumulation and Zn redistribution in tissues of suckling rats. Zn testicular depletion during lactation seems also to be due to its sequestration by Cd-induced hepatic metallothioneins (MTs) from the plasma in the organism of offspring rats, thereby increasing its concentration in the liver and kidneys and probably restricting Zn supply to other tissues [18].…”
Section: Discussionmentioning
confidence: 89%
“…The protective effect of Zn against Cd-induced testicular damage may be due to interaction between the two metals at three major sites: small intestine, liver and testis. In the small intestine, enhanced consumption of Zn may decrease Cd absorption from the digestive tract and its accumulation in the offspring rat's organism, and as a result, it may protect against the toxic effects of Cd [15]. In the liver, interaction between Cd and Zn to induce MTs which sequesters Cd had been suggested as the most likely mechanisms [18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quantification of the GFP expression in the tg‐(cyp19a1b‐GFP) zebrafish in multiple field of view mode was performed as previously reported (Brion et al , ) and confirmed the protective effect of Zn (data not shown). Although Zn concentrations were not measured in fish and culture cells used in this study, it is possible that the protection provided by this oligoelement against Cd‐induced toxicity might result from an increase of Zn availability due to Zn supplementation as reported by some authors (Chemek et al , ; Chouchene et al , ). The correction observed at the zfERs transactivation level leads to think that the Zn finger motifs could be involved at first in Cd toxicity and later in Zn protection.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, cadmium is one of the most toxic metals classified by International Agency for Research on Cancer as a human carcinogen. It has no biological function (Jones and Gadd 1990;Chemek et al 2015) and can exert toxic effects at low concentrations, including inhibition of growth (Rani et al 2013) and cell death (Kim et al 2013). It is considered genotoxic and carcinogenic for lung, kidney, and prostate (Navarro Silvera and Rohan 2007;Stone 2008).…”
Section: Introductionmentioning
confidence: 99%